Identifying Motor, Emotional–Behavioral, and Cognitive Deficits that Comprise the Triad of HD Symptoms from Patient, Caregiver, and Provider Perspectives - Victorson, David (Columbia University Libraries/Information Services, 2014)
BACKGROUND: The objective of this study was to identify important attributes associated with the triad of symptoms (cognition, emotional–behavioral, and motor) of Huntington's disease (HD) from patient, caregiver, and medical provider perspectives to facilitate development of a new disease-specific, health-related quality of life (HRQOL) instrument. METHODS: We conducted a targeted literature review of HD and HRQOL instruments, expert surveys, and patient and caregiver phone-based interviews to extract information on the symptoms and issues most relevant to the HD symptom triad (HD triad). The data collected from these sources were used to generate themes and subdomains and to develop an integrated schema that highlights the key dimensions of the triad. RESULTS: The search identified the following areas: emotional functioning/behavioral changes (e.g., positive emotions, sadness/depression); cognitive functioning (e.g., memory/learning, attention/comprehension); physical functioning (e.g., motor functioning, medication); social functioning (e.g., leisure, interpersonal relationships); end-of-life concerns/planning; and gene testing. Fifteen individuals diagnosed with HD and 16 HD caregivers, recruited from several Huntington's Disease Society of America support group networks, completed phone interviews. Nineteen US medical providers who specialize in HD completed the online survey. Twenty-six subdomains of the HD symptom triad (seven cognition, 12 emotional–behavioral, and seven motor) emerged relatively consistently across patient, caregiver, and provider samples. These included movements/chorea, memory impairment, depression, and anxiety. DISCUSSION: Based on an integrated, mixed-methods approach, important HD triad symptom were identified and organized into a guiding schema. These patient-, caregiver-, and provider-triangulated data served as the basis for development of a HD-specific HRQOL instrument, the HD-PRO-TRIAD™.